Musculoskeletal Ultrasound-Guided Regenerative Medicine - El Miedany, Yasser; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book examines recent developments in regenerative medicine and the use of musculoskeletal ultrasound. Musculoskeletal regeneration has become a prominent research topic, no doubt due to the sociological and economic pressures imposed by the current ageing population. The ever expanding role of regenerative medicine and the identification as well as characterization of stem cells have introduced a major paradigm shift in the field of musculoskeletal and sports medicine as well as orthopaedic surgery. Whereas in the past, diseased tissue was replaced with allograft material, current trends in research revolve around regenerating damaged tissue. Specifically, regenerative medicine stands in contrast to the standard treatment modalities which impair the body$1 (Bs natural abilities to facilitate endogenous repair mechanisms such as anti-inflammatory drugs; or destructive modalities (e.g., radiotherapy, nerve ablation, injections of botulinum toxin) and surgical interventions that permanently alter the functioning of a joint, bone or spine. When compared to other allopathic options (including knee and hip arthroplasty with a 90-day mortality rate of 0.7%), regenerative medicine treatment modalities have a lower incidence of adverse events with a growing body of statistically significant medical literature illustrating both their safety and efficacy. Focusing on the major values of regenerative medicine, this book with its 21 chapters is expected to fill an important void in the current literature. It will take that extra step to guide you in your day to day clinical practice. Featuring contributions from a large international group of leaders in regenerative medicine and musculoskeletal ultrasonography, this book is an authoritative reference for rheumatologists, physiatrists, sonographers, radiologists, physiotherapists and orthopaedic specialists.s
Part I. Regenerative Medicine -- Chapter 1. Advances in Regenerative Medicine -- Chapter 2. Regenerative Medicine Options for Musculoskeletal Ultrasound -- Chapter 3. Translational Regenerative Medicine -- Part II. Diagnostic and Interventional Musculoskeletal Ultrasonography -- Chapter 4. Image Optimization -- Chapter 5. Shoulder -- Chapter 6. Elbow -- Chapter 7. Wrist and Hand -- Chapter 8. Hip -- Chapter 9. Knee -- Chapter 10. Foot and Ankle -- Part III. Back and Spine -- Chapter 11. Spine -- Chapter 12. SPINAL REGENERATIVE MEDICINE -- Part IV -- Chapter 13. Regenerative Medicine in Dentistry -- Part V Musculoskeletal ultrasound in Regenerative Medicine -- Chapter 14. Regenerative Medicine Procedures under Ultrasound Guidance -- Chapter 15. Peripheral Nerve Hydrodissection -- Chapter 16. High Frequency Peripheral Nerve Ultrasound -- Chapter 17. Neural Prolotherapy under Ultrasound Guidance -- Chapter 18. Ultrasound-Guided Spinal Procedures -- Chapter 19. Musculoskeletal US for Interventional Physiatry -- Part VI Sports Medicine -- Chapter 20. Ultrasound-Guided Exercises -- Chapter 21. Musculoskeletal US in Sports, and Orthopedic Medicine: advantages, indications and limitations -- Chapter 22. Use of musculoskeletal US and Regenerative Therapies in Sports -- Part VII Future of Regenerative medicine -- Chapter 23. Regenerative Medicine: challenges, perspective, and future directions.
Keywords: Rheumatology; Radiology; Physical therapy; Rheumatology; Radiology; Physiotherapy; Musculoskeletal Physiological Phenomena; Regenerative Medicine; Ultrasonography, Interventional